Chemical analysis of multicellular tumour spheroids. Issue 12 (21st June 2015) - Jamieson, L. E.; Harrison, D. J.; Campbell, C. J.
<x xml:space="preserve">Abstract</x> Analytical chemistry applied to 3D tissue culture models.